ANALYZING OF BARRIERS AND STRATEGIES TO IMPLEMENT SUSTAINABLE MANUFACTURING IN INDONESIAN SMALL AND MEDIUM INDUSTRIES USING FUZZY AHP AND FUZZY TOPSIS - Sentana Iskandar, Dudi
Small and Medium Industries (SMIs) in Indonesia play a pivotal role in the national economy, yet they fase significant challenges in adopting sustainable manufacturing (SM) practices. These practices are essential not only for environmental stewardship but also for long-term economic competitiveness and social well-being. This tesis investigates the barriers hindering SM adoption within Indonesian SMIs, focusing on Java Island, and proposes strategic approaches to overcome them. Employing the Fuzzy Analytic Hierarchy Process (FAHP) and the Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (FTOPSIS), this study systematically identifies and prioritizes the most critical barriers. Key findings reveal that lack of consumer awareness and interest, limited manufacturing technologies, high initial costs, limited financial resources, lack of understanding and knowledge are 5 (five) major barriers. To address these challenges, this research proposes a comprehensive set of strategies, including improving financial policies and incentives, fostering collaborative research and development, advocating for supportive policies, and implementing capacity-building programs. These strategies aim to iii nllis an enabling environment for SMIs to transition towards sustainable practices. Furthermore, an in-depth case study on CV. ABC, a batik SMI, demonstrates how the Advanced SWOT analysis, integrating FAHP and FTOPSIS results, can be concretely applied to design strategies for overcoming obstacles in achieving sustainable manufacturing. By combining the company's strengths with external opportunities, and addressing internal weaknesses and external threats, this approach proves the effectiveness of a tailored, evidence-based approach. The findings of this study emphasize the necessity of a comprehensive and integrated strategy to promote sustainable manufacturing practices within Indonesian SMIs. The proposed strategy includes financial support, technological